2013
DOI: 10.1186/1916-0216-42-5
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology, antibiotic resistance and post-discharge course of peritonsillar abscesses in London, Ontario

Abstract: BackgroundPeritonsillar abscesses (PTA) are a common complication of tonsillitis. Recent global epidemiological data regarding PTAs have demonstrated increasing antimicrobial resistance patterns. No similar studies have been conducted in Canada and no Canadian study has examined the post-discharge course of treated patients.MethodsA prospective observational study of the epidemiology, antibiotic resistance and post-discharge course of patients presenting with a peritonsillar abscess to the Emergency Department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
57
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 15 publications
6
57
0
1
Order By: Relevance
“…In the current patient population, the mean duration between symptom onset and resolution of symptoms of 3.2 days and the mean duration between symptom onset and complete recovery from the disease of 5.5 days were comparable with findings from other studies [9,10]. The male:female ratio of patients with PTA in the present study was 2.9:1, again consistent with previous reports [2,11].…”
Section: Discussionsupporting
confidence: 92%
“…In the current patient population, the mean duration between symptom onset and resolution of symptoms of 3.2 days and the mean duration between symptom onset and complete recovery from the disease of 5.5 days were comparable with findings from other studies [9,10]. The male:female ratio of patients with PTA in the present study was 2.9:1, again consistent with previous reports [2,11].…”
Section: Discussionsupporting
confidence: 92%
“…Selective pressure from the common and not always well grounded use of macrolides in childhood leads to fast expansion of streptococcal strains with limited or absent susceptibility towards these antibiotics, which could lead to serious complications and sequels after infections caused by them (16)(17)(18)(19)(20). Confirmed data for appearance of new more virulent strains of М. сatarrhalis with obligatory production of ß-lactamase during the last years have been published even in Bulgaria (8,12).…”
Section: Discussionmentioning
confidence: 98%
“…This happens especially in cases with bacterial biofilm formation, where bacterial metabolism is amplified and thus the host immune defense system is more hampered by these more virulent bacterial species (2,10). In such cases the infection process, from upper respiratory tract mucus, propagates outside the initial localization and leads to complications such as middle ear infections or pneumonia, in some cases even it can lead to bacteremia or infections of central nervous system (2,18,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some trials it becomes obvious that mainly male adolescents and adults are affected [56], [57], [58], with a ratio of 3:1 [53], [59]. There are other investigations that do not reveal a gender-related preponderance [49], [52], [53], [55], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68]. The present study confirmed the finding, that patients younger than 19 years of age were predominantly female [53], [55], [58].…”
Section: Discussionmentioning
confidence: 99%